Warisan kuliner pempek: perpaduan budaya melayu dan tionghoa di Kota Palembang - Afni, Aisyah Nur (Maliki Interdisciplinary Journal, 2025)
Palembang pempek is one of Indonesia’s traditional cuisines that symbolizes the acculturation of Malay and Chinese cultures. This article aims to explore the process of cultural acculturation that occurs in pempek culinary, including its origins, transformation of ingredients and recipes, as well as the cultural meanings attached to this food. This research uses a qualitative approach with a descriptive-analytical method based on historical data, interviews with local culinary industry players, and literature review. The results show that pempek is not only a specialty food, but also a tangible evidence of harmonious cultural interaction in Palembang. The original recipe influenced by Chinese cooking techniques has been transformed with a touch of local Malay ingredients, creating a unique culinary identity. This article emphasizes the importance of maintaining the sustainability of culinary traditions as part of a shared cultural heritage.